2022
DOI: 10.1021/acssuschemeng.1c05289
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Quantitative Determination of Virgin and Recycled Cashmere: a Near-Infrared Spectroscopy Study

Abstract: Cashmere plays an important role in luxury fashion due to its characteristics of fineness, warmth, and softness. In the frame of "green economy", many companies have started to produce and market recycled cashmere textiles. Recycled cashmere is derived from postfactory and post-consumer waste. The mechanical action involved in recycling cashmere causes severe damage to the fibers, affecting their morphological and mechanical properties. In order to safeguard the consumers and the companies from possible adulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…When the activity is assessed, given that TIMPs have already affected the MMPs' activity, is it still necessary to also determine the TIMPs level? The literature contains some statements about the relationship between proteases and their inhibitors in wound healing, such as the excess of proteases over their inhibitors [91] or the imbalance between proteases and their inhibitors. [92,93] The latter statement may be supported by some studies, such as the one by Vaalamo et al, who found that TIMP-1 mRNA was present in acute wounds but not in chronic wounds, [90] but still more evidence is required to consider the disturbed balance between proteases and their inhibitors and also its involvement in the chronicity of the wounds as a fact.…”
Section: Effect Of Age On Protease Expressionmentioning
confidence: 99%
“…When the activity is assessed, given that TIMPs have already affected the MMPs' activity, is it still necessary to also determine the TIMPs level? The literature contains some statements about the relationship between proteases and their inhibitors in wound healing, such as the excess of proteases over their inhibitors [91] or the imbalance between proteases and their inhibitors. [92,93] The latter statement may be supported by some studies, such as the one by Vaalamo et al, who found that TIMP-1 mRNA was present in acute wounds but not in chronic wounds, [90] but still more evidence is required to consider the disturbed balance between proteases and their inhibitors and also its involvement in the chronicity of the wounds as a fact.…”
Section: Effect Of Age On Protease Expressionmentioning
confidence: 99%
“…Even more in detail, NIR spectroscopy was proposed to discriminate among varieties of cashmere material [108] and to distinguish between virgin and recycled cashmere fibers [109]. In conclusion, NIR spectroscopy is a fast and non-destructive analysis that needs long and accurate calibration work, and it is valuable to sectors where a large number of textile samples must be tested, such as quality control in large enterprises and in import/export business.…”
Section: Spectroscopymentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20] However, just like thermoplastic reprocessing, performance deterioration is unavoidable after multiple cycles of reprocessing due to chain scission, degradation, and oxidation. [21][22][23][24] Depolymerizing the vitrimer back to the original feedstocks could be an attractive strategy to enable the "monomer-polymermonomer" closed-loop cycle, but it is challenging to achieve. In some instances, vitrimers have been shown to degrade into oligomers and small molecules.…”
Section: Introductionmentioning
confidence: 99%